Legalitas Perkawinan Beda Agama: Perbandingan Antara Thailand Dan Uni Emirat Arab - Nurdiansyah, Putra Pandu Dinata (Maqasid: Jurnal Studi Hukum Islam, 2025)
Interfaith marriage is a complex social phenomenon with significant legal implications in many countries. In the context of globalization and increased human mobility, interactions between individuals from different religious backgrounds are increasingly common, including in the context of marriage. However, the legal acceptance and regulation of interfaith marriages vary widely around the world, including in Thailand and Uni Emirat Arab, two countries with very different legal and cultural backgrounds. The purpose of this study is to understand how the actual conditions of the legality of interfaith marriage exist in the legislation in Thailand and Uni Emirat Arab. The type of research used is normative legal research with a comparative approach. Interfaith marriages in Thailand and Uni Emirat Arab have different approaches according to the legal and social framework of each country. In Thailand, interfaith marriage is not explicitly regulated in the law, but couples of different religions can marry as long as they fulfill certain requirements, although often the marriages are performed in accordance with the teachings of their respective religions. Meanwhile, in Uni Emirat Arab, marriages are governed by various religious legal systems that vary according to the religious community of the marrying couple